Fabrication of metal complex phthalocyanine and porphyrin nanoparticle aqueous colloids by pulsed laser fragmentation in liquid and their potential application to a photosensitizer for photodynamic therapy - Himeda, Taisei; Kunitomi, Risako; Nabeya, Ryosuke; Zako, Tamotsu; Asahi, Tsuyoshi (Beilstein Journal of Nanotechnology, 2025)
We prepared stable nanoparticle dispersions of metal complex phthalocyanines (MPcs; M = AlCl, Fe, Co, Zn) and Pt complex octaethylporphyrin (PtOEP) by nanosecond laser fragmentation of the corresponding microcrystalline powders in an aqueous solution of the amphiphilic polymer Pluronic® F-127. All nanoparticles dispersed stably in phosphate-buffered saline and cell culture media without any precipitation for longer than one week. The aqueous F-127 solution at 0.1 wt % concentration, which is about one tenth of the critical micelle concentration, was enough to fabricate nanoparticles with excellent dispersion stability and high production efficiency. We examined the photosensitized generation of reactive oxygen species by AlClPc, ZnPc, and PtOEP nanoparticles and the photocytotoxicity for PC12 and HeLa cells, and demonstrated that the nanoparticles can be used as photosensitizers for photodynamic therapy.
Keywords: aqueous colloid; photosensitizer; phthalocyanine; pulsed laser fragmentation in liquids; reactive oxygen species generation